The Issue of Weak Hadiths ın Omer Al-Nasefi's Work El-Teysîr Fi't-Tefsîr On The Virtues (Of Fatiha İn Particular) - Gökmen, Mustafa (Fırat University, 2024)
The issue of acting on weak hadiths has been a debated issue throughout history. Scholars have adopted different views on this issue. While there are scholars who argue that weak hadiths should not be acted upon at all, there are also scholars who argue that there is no harm in acting upon them under certain conditions. While scholars such as Müslim, Yahya b. Ma'in and Subhi Salih in the modern period adopt the view that weak hadiths should not be acted upon, Imam Şafiî, Imam Ahmed and Ebu Davud prefer the view that if there is no sound hadith on a subject, weak hadiths should be acted upon. Apart from these two groups, there are also scholars, such as Ibn Hajar, who adopt the middle path and emphasize that weak hadiths should be acted upon under certain conditions. It is seen that the approaches expressing their opinions on the issue of acting on weak hadiths generally differ depending on whether the topics are provisions or virtues. While some scholars do not consider it permissible to act on weak hadiths, whether they are subject to provisions or not; It is seen that some of them are of the opinion that, under certain conditions, virtues and even provisions can be acted upon when necessary. Although the Scholars are generally of the opinion that one should not act on a weak hadith regarding the provisions, some of them stated that there is no harm in acting on it if it meets certain conditions regarding the provisions. Acting with weak hadiths regarding virtue has been a subject mentioned by many scholars. It has been seen that many hadith scholars, from the early periods, have adopted a positive attitude towards hadith narrations regarding virtue. This shows that the idea of acting with weak hadiths has existed since then. Ulama who follow the Hanafi sect generally made inferences based on weak hadiths. It is seen that Hanafi scholars, who attach importance to ray and qiyas, prefer weak hadiths to ray and qiyas in some cases. This situation is mostly the result of the necessity of extracting the provisions regarding ta'abbudi issues from the hadiths. It is also possible that they use weak hadiths in order to encourage people to do good and avoid bad situations regarding the virtue of deeds. In some cases, the use of hadiths that are in accordance with precautions is a common situation among Hanafi scholars. For this and similar reasons, it is possible to see the use of weak hadith among Hanafi scholars. It would not be right to limit the issue of weak hadith and deeds only to Hanafi ulema. The issue of acting with weak hadith has been discussed a lot in the sources on the Sunni hadith method. Hadith scholars have examined these hadiths under two main headings: provisions and virtues. They did not see any problems in the narration of weak hadiths, provided that they were not on matters related to belief and rules; It is possible to say that they acted more inclusively when they narrated hadiths on subjects such as maw'iza, virtue of deeds and stories, as well as issues related to tafsir and megazi. Weak hadith narration and acting on weak hadith, and some scholars preferring weak hadiths to qiyas, indicate that this is because it is attributed to the Prophet Muhammad. Commentators generally give a lot of space to weak hadiths, fabricated news andİsraelites in their tafsir books. In particular, it is seen that the commentators of narration use every material they find about the virtues of the suras, without evaluating their authenticity. It is seen that Muhaddith scholars frequently resort to weak hadiths as well as sound narrations, especially on subjects such as fedailu'l-quran, fedailu's-suver, fedailu'l-ayat. In this context, if the hadiths used by Nasafi regarding the virtues of the suras in his work called et-Teysîr fi't-tefsîr are examined, it will be seen that he gives a lot of place to weak hadiths. It is important that, in addition to the scholars who adopt the view that weak hadiths cannot be acted upon, there are also scholars such as Nasafi, who believe that there is no harm in acting on weak hadiths on some issues, especially regarding virtues. As a matter of fact, although the fact that Nasafi was a muhaddith as well as a commentator gave the impression that he would select and use the hadiths more meticulously, it has been observed that he did not behave differently from other commentators and used weak hadiths and fabricated news about the virtues of the suras. In this respect, it is seen that Nasefi reflects the general attitude of commentators in his work. It is possible to see that a scholar who is knowledgeable in many fields resorts to weak hadiths, especially regarding virtues, shows a moderate approach to the status of these hadiths, and accepts that weak hadiths are suitable for narration and can be acted upon.

Zayıf hadislerle amel hususu tarih boyunca tartışılan bir konu olmuştur. Bu konuda âlimler farklı görüşler benimsemişlerdir. Zayıf hadislerle mutlak surette amel edilmemesi gerektiğini savunan âlimler olduğu gibi, bazı şartlar muvacehesinde amel edilmesinde sakınca olmadığını savunan âlimler de mevcuttur. Yahya b. Maîn (v.233), Müslim (v.261) ve modern dönemde Subhi Salih gibi ulema zayıf hadisle amel edilmeyeceği görüşünü benimserken, İmam Şafiî (v.204), İmam Ahmed (v.241) ve Ebû Dâvud (v.275) ise bir konuda sahih hadis bulunmadığı takdirde zayıf hadisle amel edilmesi gerektiği görüşünü tercih etmektedirler. Bu iki grup haricinde, İbn Hacer (v.852) gibi orta yolu benimseyen ve bazı şartlar çerçevesinde zayıf hadisle amel edilmesi gerektiği vurgusunu yapan âlimler de bulunmaktadır. Zayıf hadisle amel etme meselesinde görüş beyan eden yaklaşımların genellikle konuların ahkâm veya faziletler olmasına göre farklılık arz ettiği görülmektedir. Bazı âlimler ister ahkâm konusu olsun ister olmasın zayıf hadisle amel etmeyi caiz olarak görmezken; bazılarının ise belli şartlar dâhilinde faziletler hatta gerektiğinde ahkâm konusunda dahi onlarla amel edilebileceği kanaatini taşıdıkları görülmektedir. Ulema genel itibariyle ahkâm konusunda zayıf hadisle amel edilmemesi kanaatine sahip olsa da bazıları ahkâm konusunda birtakım şartlar taşıması durumunda amel edilmesinde sakınca olmadığını belirtmişlerdir. Fezâile dair zayıf hadislerle amel birçok âlim tarafından dile getirilen bir konu olmuştur. İlk dönemlerden itibaren pek çok hadisçinin fazilet konusunda hadis rivayetine mütesâhil bir tavır takındıkları görülmektedir. Bu durum zayıf hadislerle amel düşüncesinin o zamandan beri var olduğunu göstermektedir. Hanefi mezhebine müntesip olan ulema genel itibariyle zayıf hadisler ile istidlalde bulunmuşlardır. Rey ve kıyasa önem veren Hanefî âlimler bazı durumlarda zayıf hadisi rey ve kıyasa tercih ettikleri görülmektedir. Bu durum daha çok taabbudi konular ile ilgili hükümleri hadislerden çıkarma zorunluluğu sonucu ortaya çıkmaktadır. Ayrıca amellerin fazileti hususunda insanları iyiliğe teşvik edip kötü durumlardan sakındırmak maksadıyla zayıf hadisleri kullanmaları da söz konusudur. Bazı durumlarda ise ihtiyata uygun olan hadislerin kullanımı Hanefi ulema arasında yaygın olan bir durum olarak göze çarpmaktadır. Bu ve bunlara benzer sebeplerden ötürü zayıf hadis kullanımını Hanefî ulemâ arasında görmek mümkündür. Zayıf hadisle amel meselesini sadece Hanefi ulema ile sınırlandırmak doğru olmaz. Sünni hadis usulüne dair kaynaklarda zayıf hadisle amel meselesi çokça tartışılmıştır. Hadisçiler bu hadisleri ahkâm ve faziletler olmak üzere iki ana başlık altında irdelemişlerdir. Akaid ve ahkâma dair konularda olmamak şartıyla zayıf hadislerin rivayetinde problem görmemişlerdir; mev’iza, amellerin fazileti ve kıssalar gibi konularda, tefsir ve megaziye ait hususlarda hadis rivayet ettiklerinde daha mütesahil davrandıklarını söylemek mümkündür. Zayıf hadis rivayeti ve zayıf hadisle amel edilmesi, bazı ulemanın zayıf hadisleri kıyasa tercih etmeleri o rivayetin Hz. Peygamber’e nispet edilmesi dolayısıyladır. Müfessirler kaleme aldıkları tefsirlerinde genel olarak zayıf hadislere, uydurma haberlere ve israiliyata oldukça fazla yer vermektedir. Özellikle rivayet tefsiri sahibi müfessirlerin sıhhat değerlendirmesi yapmaksızın surelerin fazileti hakkında buldukları her malzemeyi kullandıkları görülmektedir. Muhaddisler de özellikle fedâilu’l-kur’an, fedâilu’s-suver, fedâilu’l-âyât gibi konularda sahih rivayetlerin yanı sıra zayıf hadislere oldukça fazla başvurdukları görülmektedir. Bu minvalde Nesefî’nin et-Teysîr fi’t-tefsîr adındaki eserinde sûrelerin faziletine dair kullandığı hadisler incelendiği takdirde zayıf hadislere oldukça fazla yer verdiği görülecektir. Zayıf hadislerle amel edilmez görüşünü benimseyen ulemanın yanı sıra bazı konularda zayıf hadislerle özellikle faziletler hususunda amel etmekte bir sakınca olmadığı kanaatinde olan Nesefî gibi âlimlerin de söz konusu olması önemi haizdir. Nitekim Nesefî’nin müfessir özelliğinin yanı sıra muhaddis olması, hadisleri daha titiz bir şekilde seçip kullanacağı intibası uyandırsa da kendisinin diğer müfessirlerden farklı davranmadığı, zayıf hadisleri ve uydurma haberleri surelerin fazileti hususunda kullandığı gözlemlenmiştir. Bu bakımdan Nesefî’nin müfessirlerin genel tavrını eserine yansıttığı görülmektedir. Pek çok alana vakıf olan bir âlimin özellikle faziletler hususunda zayıf hadislere başvurması, bu hadislerin konumu hakkında ılımlı bir yaklaşım sergilediği, zayıf hadislerin rivayete elverişli olduğunu ve amel edilebilir olduklarını kabul ettiğini göstermesi açısından önem arz etmektedir.
Ömer En-Nesefî’nin Et-Teysîr Fi’t-Tefsîr’inde Sûrelerin Faziletine Dâir Zayıf Hadisleri Kullanması (Fâtiha Sûresi Özelinde)
Keywords: Hadith; Hadis